(untitled) (Fiep Bulletin - online, 2013)
The study has the objective of characterizing the types of complaints with the services of protection to the elderly and emphasizing the complaints filed, particularly in the health field. This is a documentary study conducted on the basis of complaints filed documents in the years 2005 and 2006, next to the bodies of protecting the elderly, based on the rights protected in the Constitution, Civil Code and Brazilian National Policy of Aged, in particular, the rights to health. The material collected was subjected to content analysis thematic categories. The results showed six categories of analysis: social, public order, health, welfare, violence, legal and other claims.